ChemInform Abstract: A Concise Synthesis of the AB‐Ring Fragment of (‐)‐Gambierol. Issue 17 (4th April 2013) - Fuwa, Haruhiko; Hirota, Kazuaki; Sasaki, Makoto
Abstract via a silver‐catalyzed endo‐cyclization of hydroxy ynone (II) as a key step